The Supervised Internship I in the conception of the Chemistry Degree students: Analysis of the responses to the Curriculum Internship Supervision questionnaire (Research, Society and Development, 2021)
The Supervised Curricular Internship is essential for the formation of undergraduate students in Chemistry, as it offers conditions for the application of academic knowledge, providing opportunities for the practice of skills and the development of a critical view of teaching performance. The objective of this work was an analysis of the answers to the questionnaire applied to Stage I graduates, carried out remotely in public schools in the city of Paraíso do Tocantins. The research was carried out with the participation of 8 (eight) academics. The virtual questionnaire was built on the Google Forms platform, with objective and discursive questions. The analysis of the questionnaire showed that students performed internships in public schools, with excellent guidance, good supervision and information about the procedures and evaluation of the internship, considered significant the knowledge obtained in the course subjects during and before the internship. Provided assurance of classroom performance. The evaluation of the internship environment was good and the professors carried out the annual planning with adaptations, transmitting the planned contents using video classes as a technological resource and that most professors in the internship units did not have training or knowledge in TDIC. The importance of carrying out Practice I for teacher education is summed up in providing opportunities for experiences in loco, awakening reflection, criticality and scientific research so that students can start their teaching career with a more solid training.